Hybrid off-grid renewable power system for sustainable rural electrification in Benin. (January 2020) - Odou, Oluwarotimi Delano Thierry; Bhandari, Ramchandra; Adamou, Rabani
Abstract: Providing power to rural communities, which are far from the grid and suffer from lack of energy access in Africa, especially in Benin, in a sustainable manner requires the adoption of appropriate technology. This paper aims at analysing the techno-economic feasibility of hybrid renewable energy system (HRES) for sustainable rural electrification in Benin, using a case study of Fouay village. HOMER software is used to perform optimization, simulation and sensitivity analysis. The analysis showed that hybrid solar photovoltaics (PV)/diesel generator (DG)/battery (of 150 kW/62.5 kVA/637 kWh) is the least cost optimal system. This system ensures a reliable power supply, reduces battery requirements by 70% compared to PV/battery system and achieves 97% CO2 emissions reduction compared to a conventional DG. Moreover, the study demonstrated that the most economical HRES depends strongly on the potential energy sources available at a location and power plant's remoteness from the beneficiary. In summary, as solar radiation is an abundant resource across the country, this hybrid PV/DG/battery system can be a suitable model to power remote areas in Benin, and we recommend it for future electrification projects in the country in place of the current widely deployed PV/battery system. Highlights: PV/DG/battery is the least costly system with a COE of 0.207/kWh. HRES (PV/DG/battery) reduces battery storage requirements by 70%. PV/DG/battery system has a short payback period of 3.45 years and a high IRR of 33.3%. The robustness of the system is discussed by performing the sensitivity analysis. Optimised HRES (PV/DG/battery) is economically more viable than grid extension.